Designing a program to address the basic musicianship needs of church organists of Our Lady of Hope Parish. - Lim, Engracia Reyes
The program, as designed, will provide those with little or no musical background an opportunity to learn, read and play keyboard music, thus enabling them to serve the parish as church organists. Moreover, they will be knowledgeable about the liturgical music guidelines and repertoire to help fulfill the parish music ministry's mission of evangelization through sacred music. More trained church organists can use both the Yamaha Clavinova and the beautiful Hammond organ in the church with their majestic sounds to enhance the usual guitar accompaniments of Holy Masses especially on Sundays and feast days. This program may be adopted by other parishes that are similarly in need of training for church organists.